Comparative experiments and effectiveness evaluation on vertical blowing fans (VBF) for frost protection - Yongguang, Hu; Wenye, Wu; De Melo-Abreu, J. Paulo; Shapland, Tom M.; Hong, Zhang; Snyder, Richard L. (International Journal of Agricultural and Biological Engineering, 2015)
Experiments were conducted to evaluate the performance of vertical blowing fans (VBF) for frost protection in a vineyard on a steep slope near Napa Valley in Northern California, USA, and a tea plantation located on undulating terrain in Zhenjiang, China. Minimum temperature comparisons from within the grape vineyard on nights with and without VBF operation with control station minimum temperatures exhibited no temperature benefit. Profile measurements from the test in China indicated that there was an increase in temperature when the VBF was first started, but that benefit was lost over time. No clear benefit from using the VBF was observed. Observation of frost deposition and thermal imagery also showed no benefit except for within about 5 m of the VBF. Based on this work, the effectiveness of the VBF for frost protection was not validated.Keywords: frost protection, thermal inversion, weather modification, wind machines, vertical blowing fans (VBF), temperatureDOI: 10.3965/j.ijabe.20150805.1419Citation: Hu Y G, Wu W Y, De Melo-Abreu J P, Shapland T M, Zhang H, Snyder R L. Comparative experiments and effectiveness evaluation on vertical blowing fans (VBF) for frost protection. Int J Agric & Biol Eng, 2015; 8(5): 36－42.